(untitled) (Docentes 2.0 Journal, 2019)
There are different approaches from which globalization can be observed, the first approach is that which implies equal opportunities for all countries, while the second approach denies any possibility that one country has an advantage over another and the last approach, totally In contrast to the latter, a country is affected or benefited based on its economic and political forces worldwide, and not only this but also based on the changes that take place within the less developed nations.